2018
DOI: 10.7554/elife.37202
|View full text |Cite
|
Sign up to set email alerts
|

tp53 deficiency causes a wide tumor spectrum and increases embryonal rhabdomyosarcoma metastasis in zebrafish

Abstract: The TP53 tumor-suppressor gene is mutated in >50% of human tumors and Li-Fraumeni patients with germ line inactivation are predisposed to developing cancer. Here, we generated tp53 deleted zebrafish that spontaneously develop malignant peripheral nerve-sheath tumors, angiosarcomas, germ cell tumors, and an aggressive Natural Killer cell-like leukemia for which no animal model has been developed. Because the tp53 deletion was generated in syngeneic zebrafish, engraftment of fluorescent-labeled tumors could be d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
75
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(81 citation statements)
references
References 49 publications
6
75
0
Order By: Relevance
“…To definitively generate null or null-like loss-of-function zebrafish mutants, multiple exons or whole coding regions ideally should be deleted, but this approach is relatively challenging technically. It has been demonstrated that TALEN can remove up to 1Mb in zebrafish (Xiao et al 2013;Ignatius et al 2018). In this same paper, CRISPR was able to delete 1,423bps within the mir17a-mir92a region in mixed injected fish embryos (Xiao et al 2013).…”
mentioning
confidence: 76%
“…To definitively generate null or null-like loss-of-function zebrafish mutants, multiple exons or whole coding regions ideally should be deleted, but this approach is relatively challenging technically. It has been demonstrated that TALEN can remove up to 1Mb in zebrafish (Xiao et al 2013;Ignatius et al 2018). In this same paper, CRISPR was able to delete 1,423bps within the mir17a-mir92a region in mixed injected fish embryos (Xiao et al 2013).…”
mentioning
confidence: 76%
“…Despite the progress made with genomic characterization of PAX ‐fusion–positive and PAX ‐fusion–negative RMS, many important biological questions remain, including: PAX ‐fusion–positive RMS tumors show a higher propensity to metastasize compared with PAX ‐fusion–negative tumors, and loss of TP53 increases the invasive potential of PAX ‐fusion–negative RMS tumors in a zebrafish model, but what are the mechanisms that govern invasion and metastasis in PAX ‐fusion–positive and –negative RMS? The YAP/TAZ, RAS/RAF/MEK/ERK, PI3 kinase/mTOR, MYOD/MYF5, Notch, WNT, Hedgehog, and EZH2 pathways have been implicated in PAX ‐fusion–negative RMS as blocking muscle differentiation; can this knowledge be leveraged diagnostically or therapeutically? Animal modeling studies have shown that PAX ‐fusion–negative RMS can be initiated from myogenic and nonmyogenic (endothelial) precursors, while differentiating fetal myoblasts are most poised to develop PAX ‐fusion–positive RMS . Because the RMS cell of origin influences not only histological identity but also site of disease and response to therapy, what are the RMS cell(s) of origin in human disease? What is the role of immune and other cells in the tumor microenvironment in driving RMS progression, metastasis, and therapy resistance? What are the risk factors and germline mutations associated with an increased risk of RMS development? What are the most predictive preclinical models for RMS and can these be exploited for rapid and better prioritization of preclinical therapy testing? How can we best leverage new technologies, such as CRISPR‐Cas9 screening of protein domains, to identify new drug targets for RMS? What are the mechanisms by which MYOD1 L122R drives spindle cell/sclerosing RMS tumorigenesis? …”
Section: Critical Biological Problemsmentioning
confidence: 99%
“…PAX ‐fusion–positive RMS tumors show a higher propensity to metastasize compared with PAX ‐fusion–negative tumors, and loss of TP53 increases the invasive potential of PAX ‐fusion–negative RMS tumors in a zebrafish model, but what are the mechanisms that govern invasion and metastasis in PAX ‐fusion–positive and –negative RMS?…”
Section: Critical Biological Problemsmentioning
confidence: 99%
“…In regard to oncology, zebrafish displays a variety of features of a great translational value. First, it develops tumors if exposed to carcinogenic substances [15][16][17]. Second, oncogenes, tumor suppressors, and the main molecular pathways involved in cancer progression are highly conserved between zebrafish and humans [18].…”
Section: Introductionmentioning
confidence: 99%